2016
DOI: 10.1097/mcc.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia: still a major burden of disease

Abstract: Although questions remain, particularly with regard to prediction of outcome, recent studies of CAP, both clinical and experimental, have contributed novel insights into disease pathogenesis that may enable improvement of current treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As both SARS-CoV-2-associated and community-acquired pneumonias present frequently in older people (those older than 65) but their contagiousness and treatment are different, the discrimination of these entities is a high public health priority [ 15 , 16 ]. In the present case-control study with historical controls, we found that routinely collected information at the emergency department could well discriminate (with ROC AUCs above 80%) between pneumonias associated with SARS-CoV-2 and other community-acquired pneumonias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As both SARS-CoV-2-associated and community-acquired pneumonias present frequently in older people (those older than 65) but their contagiousness and treatment are different, the discrimination of these entities is a high public health priority [ 15 , 16 ]. In the present case-control study with historical controls, we found that routinely collected information at the emergency department could well discriminate (with ROC AUCs above 80%) between pneumonias associated with SARS-CoV-2 and other community-acquired pneumonias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more than half of pneumonia-related deaths occur in very old people (older than 84 years) [ 17 ]. The incidence of community-acquired pneumonia and hospitalization due to CAP is highest in adults 65 to 79 years old, and even higher in those with a known viral cause [ 16 , 19 , 20 ]. In contrast, the mean age of patients with SARS-CoV-2-associated pneumonia is much younger (50 to 60 years) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the other putative adjunctive therapies, corticosteroids currently appear to be the most promising agents on the basis of a number of recent studies and meta-analyses 98 100 . Statins and antiplatelet agents appear to be interesting because of the particular role they may play in preventing the occurrence of cardiovascular events in patients with CAP, whereas a myriad of other agents have also been mentioned, the potential benefits of which have been reviewed elsewhere 95 , 96 , 101 .…”
Section: Antibiotic and Adjunctive Therapymentioning
confidence: 99%
“…Community-acquired pneumonia (CAP) is an infectious disease with a clinical severity ranging from mild to life-threatening. CAP has high mortality rates and is costly to treat 1. In the US in 2012, the total direct medical costs related to CAP were estimated at US$ 7,220 to US$ 11,443 2.…”
Section: Introductionmentioning
confidence: 99%